Patients' Perceptions of Atrial Fibrillation, Stroke Risk, and Oral Anticoagulation Treatment: An International Survey - Lane, Deirdre A.; Meyerhoff, Juliane; Rohner, Ute; Lip, Gregory Y. H. (TH Open, 2018)
Background Global differences exist in the management of atrial fibrillation (AF), and cultural differences may influence patients' expectations and perceptions of healthcare. This survey investigated whether country-specific differences in patients' perceptions of AF and oral anticoagulation (OAC) exist and if recent stroke influences these perceptions.Methods Cross-sectional survey of 937 adults with nonvalvular AF receiving OAC for stroke prevention was conducted across United States, Canada, Germany, France, and Japan. Thirty-minute online interviews conducted between April and November 2015 included AF patients with recent stroke, and newly diagnosed AF and established AF, both without recent stroke.Results U.S. patients and those with recent stroke perceived AF as more serious (54.0 and 55.2%, respectively) and were more concerned about stroke (50.0 and 68.0%, respectively). Japanese patients were more likely to perceive AF as not serious (41.0%), but 50.4% were frequently concerned about stroke. Patients in the United States, Canada, and Germany and those without recent stroke preferred to be involved in OAC treatment decisions (either shared decision making or patient's choice), while French and Japanese patients and those with recent stroke preferred their doctor to choose. For all country groups, stroke prevention was the most important factor when choosing OAC.Conclusion In this international cohort of AF patients, country-specific differences exist in patients' perceptions of AF, concerns about stroke, and preference for involvement in OAC treatment decisions; recent experience of stroke significantly influenced patients' values and preferences regarding AF and treatment. Stroke prevention was rated as the most important factor when choosing OAC treatment.
Keywords: atrial fibrillation; oral anticoagulation; patients' perceptions; patient survey; stroke knowledge